The Perspective of Shafi'i Fiqh on the Legal Ruling of Giving a Ring in the Engagement Process - Imron, Ali; Susanti, Popi; Jaudi, La; bin Awang Tarif, Muhammad Akmal; Septiani, Rina (Institute of Education and Social Research, 2024)
Marriage is a fundamental social institution in the context of Islam. In the realm of marital customs, various traditions have emerged, including the presentation of engagement rings. The practice of giving engagement rings has become an important component of marriage proposal ceremonies, especially in Indonesia. However, according to Islamic jurisprudence, particularly within the Shafi'i school of thought, the legal standing of engagement rings requires further examination. This investigation aims to analyze the legal implications of the practice of giving engagement rings from the perspective of Shafi'i Fiqh, while also considering customary practices. The research methodology employed is a legal study with a qualitative approach. Findings indicate that Shafi'i Fiqh accommodates a wide range of customary rituals in marriage, including the exchange of engagement rings. Although there is no specific regulation governing this practice, Islam promotes marriage as a means of building a family rooted in truth, love, and compassion.